2022
DOI: 10.3389/fpubh.2022.911975
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Multi-Stage Prediction Models for Pre-eclampsia: A Retrospective Cohort Study on Chinese Women

Abstract: ObjectiveThe aim of this study is to develop multistage prediction models for pre-eclampsia (PE) covering almost the entire pregnancy period based on routine antenatal measurements and to propose a risk screening strategy.MethodsThis was a retrospective cohort study that included 20582 singleton pregnant women with the last menstruation between January 1, 2013 and December 31, 2019. Of the 20582 women, 717 (3.48%) developed pre-eclampsia, including 46 (0.22%) with early-onset pre-eclampsia and 119 (0.58%) pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 59 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…Therefore, there is a need for a concise, evidence-based, and effective tool that clinicians can use to screen women at high risk of PE in the early second trimester. This study's Previous studies have found that maternal age ≥35 years, family history of hypertension or DM, history of PE, chronic hypertension, duration of hypertension, GDM, and pre-pregnancy BMI ≥30 kg/m 2 are all associated with an increased incidence of PE (18)(19)(20)(21)(22)(23)(24)32,33). In this study, kidney disease and a family history of PE was shown to be the most important factor in predicting PE, followed by a family history of hypertension, pBMI ≥27.7 kg/m 2 , and BP ≥130/80 mmHg in the first trimester.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Therefore, there is a need for a concise, evidence-based, and effective tool that clinicians can use to screen women at high risk of PE in the early second trimester. This study's Previous studies have found that maternal age ≥35 years, family history of hypertension or DM, history of PE, chronic hypertension, duration of hypertension, GDM, and pre-pregnancy BMI ≥30 kg/m 2 are all associated with an increased incidence of PE (18)(19)(20)(21)(22)(23)(24)32,33). In this study, kidney disease and a family history of PE was shown to be the most important factor in predicting PE, followed by a family history of hypertension, pBMI ≥27.7 kg/m 2 , and BP ≥130/80 mmHg in the first trimester.…”
Section: Discussionmentioning
confidence: 64%
“…The pathogenesis of PE is complex, and its etiology is somewhat unclear (1,30,31). Numerous studies have attempted to assess the predictive performance of various factors for PE, including clinical features, biomarkers, and ultrasound indicators (18)(19)(20)(21)(22)(23)(24). Identification of early risk factors is the best way to prevent PE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preeclampsia is divided into early-onset preeclampsia and lateonset preeclampsia, based on gestational age at diagnosis or delivery. Early-onset preeclampsia, less common than late-onset preeclampsia but with more severe clinical onset features, threatens maternal and fetal health worldwide, especially in developing countries (20)(21)(22). The pathogenesis of EOPE is unclear, and an ideal early clinical biomarker for the prediction of EOPE are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…However, placental biopsy is impractical until postpartum. Even if a significant amount of research has been dedicated to separately or synergistically using maternal clinical characteristics, Doppler ultrasound indexes, blood tests, or other parameters to predict PIH, the precise early prediction of PIH remains challenging due to the lack of effective biomarkers [8][9][10][11]. Our previous study has showed that the classical early prediction biomarkers for PIH and preeclampsia, including soluble fms-like tyrosine kinase 1 (sFlt-1) and placental growth factor (PlGF), cannot be extrapolated to predict PIH occurrence in pregnancies after IVF treatment [12], suggesting the need of exploring new biomarkers for the prediction of PIH in patients who undergo IVF treatment.…”
Section: Introductionmentioning
confidence: 99%